Influence of Cirsimaritin on Anticancer Activity against HCT-116 Cell Line - Hakami, Mohammed Ageeli (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Statistics show colon cancer is the third most severe cancer type worldwide. It was discovered that there is a very high death and morbidity rate. Along with breast, prostate, lung, and colon cancer is one of the most common tumors worldwide. Objectives: Natural products have drawn interest in recent years for preventing cancer. This is due to their numerous health advantages, apparent lack of toxicity and side effects, and the limits of chemotherapeutic medicines. Numerous studies have shown that natural products have a wide range of biological effects. Materials and Methods: A flavonoid class phytochemical known as cirsimaritin, also known as 4',5-dihydroxy-6,7-dimethoxyflavone, has been discovered in the medicinal plant. The current investigation was the determination of cell proliferative XTT assay, AO/EtBr, intracellular oxygen species, Oxidative Stress Markers, and Cell cycle analysis using flow cytometry by PI analysis. Results: HCT-116 cells' cell viability was reduced with an increased concentration of cirsimaritin. ROS and apoptosis were increased with an elevated cirsimaritin concentration. Conclusion: All these results suggest that cirsimaritin can be used as a potent anticancer drug for colon cancer.
Keywords: Colon cancer; Cirsimaritin; Apoptosis; Cell viability; ROS